A Novel C-Terminal Domain of RecJ is Critical for Interaction with HerA in Deinococcus radiodurans - Cheng, Kaiying; Zhao, Ye; Chen, Xuanyi; Li, Tao; Wang, Liangyan; Xu, Hong; Tian, Bing; Hua, Yuejin (Frontiers in Microbiology, 2015)
Homologous recombination (HR) generates error-free repair products, which plays an important role in double strand break repair and replication fork rescue processes. DNA end resection, the critical step in HR, is usually performed by a series of nuclease/helicase. RecJ was identified as a 5’-3’ exonuclease involved in bacterial DNA end resection. Typical RecJ possesses a conserved DHH domain, a DHHA1 domain, and an oligonucleotide/oligosaccharide-binding (OB) fold. However, RecJs from Deinococcus-Thermus phylum, such as Deinococcus radiodurans RecJ (DrRecJ), possess an extra C-terminal domain (CTD), of which the function has not been characterized. Here, we showed that a CTD-deletion of DrRecJ (DrRecJΔC) could not restore drrecJ mutant growth and mitomycin C (MMC)-sensitive phenotypes, indicating that this domain is essential for DrRecJ in vivo. DrRecJΔC displayed reduced DNA nuclease activity and DNA binding ability. Direct interaction was identified between DrRecJ-CTD and DrHerA, which stimulates DrRecJ nuclease activity by enhancing its DNA binding affinity. Moreover, DrNurA nuclease, another partner of DrHerA, inhibited the stimulation of DrHerA on DrRecJ nuclease activity by interaction with DrHerA. Opposing growth and MMC-resistance phenotypes between the recJ and nurA mutants were observed. A novel modulation mechanism among DrRecJ, DrHerA, and DrNurA was also suggested.